The Relationship between Screen Time and Screen Size with Computer Vision Syndrome - Sisca Erlita; Nurfitri Bustamam; Sri Wahyuningsih (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
During the COVID-19 pandemic, student activities are carried out online using various gadget sizes. This situation increases the risk of computer vision syndrome (CVS). This study aims to determine the relationship between screen time and screen size with CVS among Universitas Pembangunan Nasional Veteran Jakarta medical students. The study used a cross-sectional design, questionnaire, and application to measure screen time. The study showed that 59.5% of the 84 subjects experienced CVS symptoms. The screen time of subjects on smartphones was 7.22 ± 3.01 hours/day, and on laptops 6.03 ± 3.49 hours/day. The subject uses a laptop 14 (11 - 16) inches and a smartphone 6.4 (4.7 - 6.7) inches. The Pearson correlation test showed a correlation between screen time and CVS scores (p = 0.032; r = 0.234). The Chi-square test showed there were differences in symptoms of excessive blinking between the group with laptops ≤ 14 inches and > 14 inches (p = 0.019), as well as differences in symptoms of eyes redness (p = 0.042) and blurred vision (p = 0.031) between the group with smartphones < 5.8 inches and ≥ 5.8 inches. There is a relationship between screen time and screen size with CVS.